2015
DOI: 10.1002/2015jg003025
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal to annual changes in latent, sensible heat, and CO2 fluxes over a Laurentian Great Lake: A case study in Western Lake Erie

Abstract: To understand the carbon and energy exchange between the lake surface and the atmosphere, direct measurements of latent, sensible heat, and CO 2 fluxes were taken using the eddy covariance (EC) technique in Western Lake Erie during October 2011 to September 2013. We found that the latent heat flux (LE) had a marked one-peak seasonal change in both years that differed from the diurnal course and lacked a sinusoidal dynamic common in terrestrial ecosystems. Daily mean LE was 4.8 ± 0.1 and 4.3 ± 0.2 MJ m À2 d À1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
95
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(116 citation statements)
references
References 66 publications
(127 reference statements)
16
95
4
1
Order By: Relevance
“…According to the quality control procedure presented above, around 34% of the Hs, 46% of LE and 45% of CO 2 fluxes are removed and the retained data are analyzed in our study. Although the gap ratio is large, it's similar to other studies over 5 lakes (Nordbo et al, 2012;Goldbach and Kuttler, 2015;Shao et al, 2015). A long large gap between August and November of exists in 2014 due to malfunction.…”
supporting
confidence: 74%
See 4 more Smart Citations
“…According to the quality control procedure presented above, around 34% of the Hs, 46% of LE and 45% of CO 2 fluxes are removed and the retained data are analyzed in our study. Although the gap ratio is large, it's similar to other studies over 5 lakes (Nordbo et al, 2012;Goldbach and Kuttler, 2015;Shao et al, 2015). A long large gap between August and November of exists in 2014 due to malfunction.…”
supporting
confidence: 74%
“…The rain is also observed to be closely correlated with CO 2 flux on daily scale during pre-monsoon period and on monthly scale during post-monsoon period. It has been reported that the more rain could bring more nutrients in to the water body, which will promote the photosynthesis of the phytoplankton (Shao et al, 2015). As only minor 25 rain falls during these two periods, the role of rain becomes more important.…”
Section: Main Drivers For Co 2 Flux During Different Monsoon Periodsmentioning
confidence: 99%
See 3 more Smart Citations